2022
DOI: 10.1097/fch.0000000000000312
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers and Facilitators in Accessing Cervical Cancer Screening

Abstract: Although advancements in cervical cancer prevention have helped reduce the incidence, mortality, and prevalence, access to these preventive services has not been experienced equally by all women in the United States. The purpose of this study was to learn about the factors that affect access to preventive services in a low-income, primarily Black community. Using a community-based participatory research approach, women were recruited to participate in 7 focus groups, with 6 to 8 women per group (N = 45). Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…In alignment with approaches to evaluate and modify healthcare policy, engaging in community‐based participatory research 43,44 that seeks to understand and document the lived experiences of Black women living with cancer can benefit this line of research to inform clinical practice. These community‐engaged research approaches have helped to identify barriers and facilitators to treatment for racial/ethnic minorities, 45 including as applied to cancer 46 . Lastly, it is critical to continually utilize culturally informed, systems‐level theoretical frameworks to examine and act on health disparities and health equity practices, especially for Black women living with cancer due to the unique experiences of gendered racism they experience.…”
Section: Discussionmentioning
confidence: 99%
“…In alignment with approaches to evaluate and modify healthcare policy, engaging in community‐based participatory research 43,44 that seeks to understand and document the lived experiences of Black women living with cancer can benefit this line of research to inform clinical practice. These community‐engaged research approaches have helped to identify barriers and facilitators to treatment for racial/ethnic minorities, 45 including as applied to cancer 46 . Lastly, it is critical to continually utilize culturally informed, systems‐level theoretical frameworks to examine and act on health disparities and health equity practices, especially for Black women living with cancer due to the unique experiences of gendered racism they experience.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with several international studies pointing that female providers are more likely to discuss screening and perform Pap smears than their male counterparts. (Kayser et al, 2022; Rochoy et al, 2017; Samten et al, 2021). There are also some strengths to this quality improvement project.…”
Section: Discussionmentioning
confidence: 99%
“…Another finding of this study which observed that, factors relating to the socio-cultural beliefs or locations of patients may act as barrier to their consumption of available cervical cancer treatment options has been able to shed light on how the location and sociocultural or economic advantages or disadvantages imposed of a community can limit the access to cervical cancer treatment. Earlier studies like Mantula (2022), Kayser, et al (2022) and Getachew et al (2019) have all pointed out how community-related barriers can create barrier to consumption of cervical cancer treatment measures, and hence, give credence to the current outcome.…”
Section: Discussionmentioning
confidence: 99%